Cancrum nasalis: a case report - R. A. Adewole; O. M. Gbotolorun; A. C. Olojede; O. James (Nigerian Dental Association, 2008)
Cancrum nasalis, a variant of cancrum oris, is an oro-facial condition that is rarely reported in the literature. Predisposing factors include malnutrition, infection and reduced immunity. This paper reports a case of a 10 month-old child patient who presented with an isolated necrosis of the nose extending to the cutaneous part of the upper lip without oral manifestation, a rare clinical presentation. A maculo-papular rash which was diagnosed as measles preceeded the necrosis of the nose and the child was also seen to be malnourished at presentation. Laboratory investigations and clinical management of the condition are described. It is also suggested that the public should be continuosly educated on the importance of balanced diet and routine medical check for growing children.